Cynomolgus Monkeys (Macaca fascicularis) as an Experimental Infection Model for Human Group A Rotavirus - Bentes, Gentil Arthur (2018)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Desenvolvimento Tecnológico em Virologia. Rio de Janeiro, RJ. Brasil.